Evaluasi Risiko Sistem Manajemen Keselamatan Konstruksi Berdasarkan Permen PUPR NO. 10 Tahun 2021 pada Pekerjaan Konstruksi Jalan - M Jakfar Muhti Hairi; Elvira Handayani; Annisaa Dwiretnani (Universitas Batanghari Jambi, 2022)
This study aims to determine the value of construction safety risk on the Simpang Pudak - Suak Kandis Road work. The method used in determining the value of construction safety risk is the Hazard Identification, Risk Assessment and Opportunity (IBPRP) method which refers to the PUPR Ministerial Regulation No. 10 of 2021. Based on the results of research that has been carried out a construction safety risk assessment at the Pudak - Suak Kandis Intersection Road Works based on PUPR Ministerial Regulation No. 10 in 2021 gets a Risk Value of 3.83 which is included in the category of Small Construction Safety Risk, thus the work needs to involve Construction Safety personnel with competencies as Young Construction K3 Experts / Young Construction Safety Experts; or Construction Safety Officer.